1992
DOI: 10.1002/jmri.1880020616
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac metabolism in patients with dilated and hypertrophic cardio‐myopathy: Assessment with proton‐decoupled P‐31 MR spectroscopy

Abstract: Proton-decoupled phosphorus-31 heart spectroscopy was performed in healthy subjects (n = 9) and patients with dilated cardiomyopathy (DCM, n = 9) or hypertrophic cardiomyopathy (HCM, n = 8). The phosphocreatine (PCr)-to-adenosine triphosphate ratio (+/- one standard deviation) after correction for blood contribution and partial saturation was significantly lower in HCM patients relative to the control subjects (1.32 +/- 0.29 vs 1.65 +/- 0.26, P < .05) but not in DCM patients (1.52 +/- 0.58 vs 1.65 +/- 0.26). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(57 citation statements)
references
References 22 publications
0
55
0
2
Order By: Relevance
“…39 Because CK is relatively abundant even in the failing heart, 25,28 -32,38,40 a lower total creatine pool means that [PCr] must also be lower. 31 P NMR studies in the early 1990s by several groups [41][42][43][44] showed that [PCr]/[ATP] is lower in dilated cardiomyopathy and heart failure. In Figure 2, typical 31 P NMR spectra obtained noninvasively from normal and failing human hearts illustrate the changes in [ATP] and [PCr] that characterize the failing heart.…”
Section: Pcr and The Failing Heartmentioning
confidence: 99%
“…39 Because CK is relatively abundant even in the failing heart, 25,28 -32,38,40 a lower total creatine pool means that [PCr] must also be lower. 31 P NMR studies in the early 1990s by several groups [41][42][43][44] showed that [PCr]/[ATP] is lower in dilated cardiomyopathy and heart failure. In Figure 2, typical 31 P NMR spectra obtained noninvasively from normal and failing human hearts illustrate the changes in [ATP] and [PCr] that characterize the failing heart.…”
Section: Pcr and The Failing Heartmentioning
confidence: 99%
“…We corrected ATP for the contribution originated from blood in the cardiac chambers based on a previous study (13). We corrected PCr/ATP ratios for partial saturation effects using T1 values obtained from inversion recovery experiments.…”
Section: Mrs Analysismentioning
confidence: 99%
“…Reduced CR appeared to reflect disease severity. There were previous reports examining myocardial PCr and ATP in patients with LV hypertrophy of HHD or HCM by 31 P MRS. 18 Some reports indicated that myocardial PCr/ATP ratios decreased, 19,20 while others did not. 21,22 The discrepancy may be due to differences in the Scatterplots showing the total creatine (CR) concentration in the myocardium of patients with heart disease, graded according to the New York Heart Association (NYHA) classification.…”
Section: Creatine In the Diseased Myocardiummentioning
confidence: 99%